2007
DOI: 10.1167/7.11.5
|View full text |Cite
|
Sign up to set email alerts
|

Attention changes perceived size of moving visual patterns

Abstract: Spatial attention shifts receptive fields in monkey extrastriate visual cortex toward the focus of attention (S. Ben Hamed, J. R. Duhamel, F. Bremmer, & W. Graf, 2002; C. E. Connor, J. L. Gallant, D. C. Preddie, & D. C. Van Essen, 1996; C. E. Connor, D. C. Preddie, J. L. Gallant, & D. C. Van Essen, 1997; T. Womelsdorf, K. Anton-Erxleben, F. Pieper, & S. Treue, 2006). This distortion in the retinotopic distribution of receptive fields might cause distortions in spatial perception such as an increase of the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
158
6
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(180 citation statements)
references
References 25 publications
14
158
6
2
Order By: Relevance
“…By computing the contrast that is necessary for the attended stimulus to match the apparent contrast of the unattended stimulus, this paradigm allows one to measure the change that attention effects on the perceived contrast of a stimulus. This paradigm, coupled with control experiments, has ruled out alternative cue bias and response bias explanations (9,(12)(13)(14)(15)(16)(17)(18).…”
Section: Psychophysical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…By computing the contrast that is necessary for the attended stimulus to match the apparent contrast of the unattended stimulus, this paradigm allows one to measure the change that attention effects on the perceived contrast of a stimulus. This paradigm, coupled with control experiments, has ruled out alternative cue bias and response bias explanations (9,(12)(13)(14)(15)(16)(17)(18).…”
Section: Psychophysical Studiesmentioning
confidence: 99%
“…Using this paradigm, studies have shown that exogenous attention alters our subjective impression of many dimensions of spatial and temporal vision: e.g., contrast (9,(12)(13)(14), spatial resolution (15), color saturation (16), size of moving patterns (17), and speed (18). However, the issue continues to be debated (19,20).…”
Section: Psychophysical Studiesmentioning
confidence: 99%
“…Using this paradigm, it has been reported that attention alters our subjective impression of many dimensions: contrast appearance (Carrasco, Ling, & Read, 2004;Hsieh et al, 2005), spatial frequency and gap size (Gobell & Carrasco, 2005), flicker rate (Montagna & Carrasco, 2006), motion coherence (Liu et al, 2006), size of a motion stimulus (Anton-Erxleben, Henrich, & Treue, 2007), perceived speed (Turatto et al, 2007), and color saturation (but not hue; . For a review, see Carrasco (2007).…”
Section: New York University New York New Yorkmentioning
confidence: 99%
“…We implemented a paradigm that allowed us to measure perceived contrast without asking observers to do so directly. Moreover, because our observers performed an orientation discrimination task contingent upon appearance, we had an objective index indicating that the observers were performing the task and that the cue was effective (Anton-Erxleben et al, 2007;Carrasco, Ling, & Read, 2004;Liu et al, 2006). Many have commented on the strengths of this simple paradigm (Luck, 2004;Treue, 2004).…”
Section: Direct Versus Indirect Judgments Of Appearancementioning
confidence: 99%
“…Exogenous attention has also been reported to alter the perceived coherence (Liu, Fuller, & Carrasco, 2006), size (Anton-Erxleben, Henrich, & Treue, 2007), and speed (Turatto, Vescovi, & Valsecchi, 2007) of moving objects.…”
mentioning
confidence: 99%